1980
DOI: 10.1097/00000658-198008000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Sufficiency of Regenerated Lung Lymphatics

Abstract: The physiologic sufficiency of regenerated lung lymphatics after surgical transection of the lung hilum was studied experimentally. Dogs were prepared by surgical interruption of all left lung hilar tissues and structures except the skeletonized pulmonary artery and the pulmonary veins; continuity of the bronchus was restored by anastomosis. Anatomic reconnection of lung lymphatics to mediastinal lymph vessels was determined by injecting a sky blue dye marker into peribronchial tissues distal to the bronchial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, clues come from reports published during the early days of lung transplantation of reduced lung congestion in reimplanted lungs coinciding with lymphatic regeneration and anastomosis. 82,83 In our study, widespread extravasation of platelets and fibrinogen and the large increase in lung weight after bleomycin challenge reflect an excess accumulation of fluid and cells and insufficient lymphatic clearance. Together, our findings that lung lymphatic network expansion in CCSP/ VEGF-C mice reduces lymph stasis, decreases fibrosis, and accelerates recovery from disease by increasing lymphatic clearance of fluid and cells are consistent with the mechanisms elucidated in other disease models.…”
Section: Prior Lymphatic Network Expansion Reduces Macrophage Numbers and Fibrosis And Accelerates Recovery From Lung Injurymentioning
confidence: 58%
“…However, clues come from reports published during the early days of lung transplantation of reduced lung congestion in reimplanted lungs coinciding with lymphatic regeneration and anastomosis. 82,83 In our study, widespread extravasation of platelets and fibrinogen and the large increase in lung weight after bleomycin challenge reflect an excess accumulation of fluid and cells and insufficient lymphatic clearance. Together, our findings that lung lymphatic network expansion in CCSP/ VEGF-C mice reduces lymph stasis, decreases fibrosis, and accelerates recovery from disease by increasing lymphatic clearance of fluid and cells are consistent with the mechanisms elucidated in other disease models.…”
Section: Prior Lymphatic Network Expansion Reduces Macrophage Numbers and Fibrosis And Accelerates Recovery From Lung Injurymentioning
confidence: 58%
“…This might result from increased recognition of the disorder in this population or reflect increased risks associated with lung transplantation, including the possibility of donor transmission. For example, exposure of the lung directly to the systemic venous circulation and impaired lymphatic drainage in the donor lung after transplantation have been suggested to increase the risk of pneumonia in the first 4 to 6 weeks after transplantation (1820). In support of this hypothesis, we were able to detect or culture Ureaplasma from all of the lung tissue and BAL samples collected from patients with hyperammonemia available for our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph-flow reestablishment has some intuitive appeal in this circumstance; it might reduce the extent of pulmonary vascular injury. However, lymph-flow reestablishment may not be effective acutely since the process often takes 7 ± 28 days, and does not become fully functional for approximately 35 days [67,68]. Cui [55] suggested that active lymph drainage from the lung hila, rather than other pulmonary sites, would be more effective in alleviating PLO that complicated mediastinal surgical procedures.…”
Section: Possibility Of Active Lymph Drainage In the Therapy Of Pulmomentioning
confidence: 99%